The IMMIGRANTS ARE ANIMALS metaphor as a deliberate metaphor in British and Bosnian-Herzegovinian media - Mujagić Mersina; Berberović Sanja (ExELL (Explorations in English Language and Linguistics))
Applying MIPVU (Steen et al., 2010) to the corpus of media articles about the European migrant crisis in the period from August 2015 until March 2016 in English and Bosnian/Croatian/Serbian, this paper analyzes the IMMIGRANTS ARE ANIMALS metaphor within the framework of the deliberate metaphor theory by considering the three dimensions of this metaphor, namely, the linguistic dimension of (in)directness, the conceptual parameter of conventionality, and the communicative dimension of (non)deliberateness. Specifically, the paper examines the use of the ANIMALS metaphor as a deliberate metaphor in the immigration discourse in English and Bosnian/Croatian/Serbian. The paper aims to determine to what extent and in which situations the authors of the texts tend to divert the addressee’s attention to viewing immigrants in terms of animals. Using the IDeM protocol for the identification of deliberate metaphor (Krennmayr, 2011), the paper also focuses on the rhetorical potential and the effects of the use of deliberate metaphors in the media discourse. Such metaphors are often used in the media discourse to dehumanize immigrants and consequently reduce the addressee’s empathy for them.